Pengolahan Air Limbah Laundry Menggunakan Adsorbsi Cangkang Telur Ayam - Novita Sari Fasihah; Yeyen Maryani; Heri Heriyanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
The increase in the number of washing industries each year parallels the increase in waste production. Without previous treatment, the created laundry waste will be disposed of straight into the environment, causing environmental damage. Laundry waste is characterized by high concentrations of BOD, COD, and LAS, which contribute to environmental damage. This study's objective is to treat laundry waste by adsorption using shell waste. Observed variables included powder size (50, 100, 150, and 200 mesh) and contact time (30, 60, 90 and 120 minutes). The filtrate was tested to determine the concentrations of BOD, COD, and LAS. The obtained results indicate that the optimal adsorbent size is 150 mesh, which can lower BOD levels by 80%, LAS levels by 38.85%, and COD levels by 67.34 %. The optimal period for decreasing COD and BOD levels is 90 minutes, which can reduce BOD levels by 80 percent and COD levels by 74.5 percent, and 120 minutes, which can cut LAS levels by 35.67 percent. The appropriate LAS adsorption isotherm is the Freundlich isotherm with R2 of 0.95023. The use of eggshell waste as an adsorbent demonstrates the significance of environmentally friendly waste treatment technology to laundry waste treatment.